Love knows no colour : why parents respond the same to babies of different ethnicities. An fMRI investigation - Sng, Kelly Hwee Leng (Nanyang Technological University, 2021)
Baby schema, a specific constellation of facial features in infants, are suggested to spontaneously prompt parenting behaviour and directing of affect toward infants. Although the society we live in is becoming increasingly multicultural, and the manner in which individuals from the same versus other ethnicities are perceived affects our own and societal well-being, no study has explicitly studied the neural bases of the baby schema effect in a multi-ethnic context. By focusing on the baby schema effect in Singaporean Chinese parents, this study aimed to provide a more holistic understanding of the instinctive nature of parenting. Functional magnetic resonance imaging (fMRI) was employed to compare the neural processing of parents’ (N = 23) toward non-own same-ethnic infant, non-own other-ethnic infant, and own-infant faces. Results revealed that ethnicity does not moderate the baby schema effect. Furthermore, own-infant faces (versus non-own infants) elicited widespread activation in empathic, reward and motivation, and motor intentions and control cortical networks. These results accord a more exquisite delineation of the neural networks implicated in the baby schema effect, and help to situate ethnicity within the neural space of human caregiving.